Mother Nature knew best? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Mother Nature knew best?True, Mother Nature has indeed always looked after the genetic development of organisms: and has produced some pretty nasty ones along the way, which we tend to forget. Farmers, plant and animal scientists have produced crop...